TAFSIR DAN HADIST SUKUK OBLIGASI SYARIAH (MENGUNGKAP KONSEP TRANSAKSI KEBATILAN DALAM QS. AN- NISA : 29) - Asri Sundari; Ahmad Hasan Ridwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of writing this paper is to find out whether there is falsehood in the sukuk transaction. This paper aims to see based on sharia principles as well as seen from QS. An-Nisa verse 29. The research method used in this paper is a qualitative method in the form of a literature study. Classical commentary books as primary sources and supporting theory books as secondary sources. The results of this study are ordered by Allah SWT that it forbids His believing servants to eat the wealth of some of them over others in a false way, namely through businesses that do not have the Shari'a, such as doing it by means of usury, gambling and various other ways. which fall into the category of using various tricks and deception. The author concludes that in the sukuk transaction it is clearly stated in the Qur'an and hadith that the management carried out must be based on sharia principles, it is not allowed to contain elements of maysir (gambling), gharar (obscurity), and usury (usury).